Environmental factors and stochasticity affect the fungal community structures in the water and sediments of Hulun Lake, China. Issue 11 (18th November 2022) - Shang, Yongquan; Wu, Xiaoyang; Wang, Xibao; Dou, Huashan; Wei, Qinguo; Ma, Shengchao; Sun, Guolei; Wang, Lidong; Sha, Weilai; Zhang, Honghai
Abstract: Aquatic fungi form both morphologically and ecologically diverse communities. However, lake ecosystems are frequently overlooked as fungal habitats, despite the potentially important role of fungi in matter cycling and energy flow. Hulun Lake is a typical example of a seasonal glacial lake; however, previous studies have only focused on bacteria in this ecosystem. Therefore, in the current study, internal transcribed spacer ribosomal RNA (ITS rRNA) gene high‐throughput sequencing was used to investigate the fungal communities in paired water and sediment samples from the Hulun Lake Basin in China. A significant difference was found between the fungal communities of the two sample types. Across all samples, we identified nine phyla, 30 classes, 78 orders, 177 families, and 307 genera. The dominant phyla in the lake were Ascomycota, Basidiomycota and Chytridiomycota. Our results show that both water and sediments have very high connectivity, are dominated by positive interactions, and have similar interaction patterns. The fungal community structures were found to be significantly affected by environmental factors (temperature, chemical oxygen demand, electrical conductivity, total phosphorus, and pH). In addition, the dispersal limitations of the fungi affected the structure of the fungal communities, and it was revealed that stochasticity is more important than deterministic mechanisms in influencing the structure and function of fungal communities. This study provides unique theoretical support for the study of seasonally frozen lake fungal communities and a scientific basis for the future management and protection of Hulun Lake. Abstract : The fungal community structures were found to be significantly affected by environmental factors (temperature, chemical oxygen demand, electrical conductivity, total phosphorus, and pH). In addition, the dispersal limitations of the fungi affected the structure of the fungal colonies, and it was revealed that stochasticity is more important than deterministic mechanisms in influencing the structure and function of fungal communities.